Jurnal Kata: entrapment in relationship in august strindberg's the father and harold pinter's the collection - Samira sasani, Parvin ghasemi (Prodi Bahasa Inggris Fak sastra PETRA, 2014)
modern drama is replete with defferent forms of entrapment in relationship in august strindberg's